Performance Analysis of DP-QAM-Based Optical OFDM PON Employing Optical Multicarrier - Ibrahim Luay; Tahreer Safa’a Mansour (Journal of Engineering)
This work proposes a new hybrid bidirectional standard single mode fiber (SSMF)/free space optical (FSO) dual polarization quadrature amplitude modulation (DP-QAM) employing optical orthogonal frequency division multiplexing (OFDM). An optical multicarrier generator (OMG) source is utilized. The suggested model is simulated using VPI photonics software. Thirty-two optical OFDM channels are used; each carrier’s 30 Gbps information data with DP-QAM are employed to improve the performance of the fifth-generation passive optical network (5G-PON) for downstream and upstream transmission. In addition, 16-QAM signals are used in DP. The impact of continuous wavelength (CW) lasers and high data rates in the proposed 5G-PON has been investigated for DP-QAM-OFDM. The results reveal 0.96 Tb/s and 0.1 Tb/s for the downstream and upstream directions, respectively, under different turbulence effects. Furthermore, the simulation results show that the proposed model can achieve an SSMF length and FSO propagation ranges of 20 km and 2 km, respectively, with the symbol error rate (SER) (<10−9) and error vector magnitude (EVM) (<0.186).